AN EFFECTIVE SECURE ENVIRONMENT USING GRAPHICAL PASSWORD AUTHENTICATION SCHEME (International Journal of Engineering and Computer Science, 2017)
Authentication, authorization and auditing are the most important issues of security on data communication. In particular, authentication is the life of every individual essential closest friend. The user authentication security is dependent on the strength of user password. A secure password is usually random, strange, very long and difficult to remember. For most users, remember these irregular passwords are very difficult. To easily remember and security are two sides of one coin. In this paper, we propose a new graphical password authentication protocol to solve this problem. Graphical password authentication technology is the use of click on the image to replace input some characters. The graphical user interface can help user easy to create and remember their secure passwords. However, in the graphical password system based on images can provide an alternative password, but too many images will be a large database to store issue. All the information can be steganography to achieve our scheme to solve the problem of database storage. Furthermore, tabular steganography technique can achieve our scheme to solve the information eavesdropping problem during data transmission. Our modified graphical password system can help user easily and friendly to memorize their password and without loss of any security of authentication. User’s chosen input will be hidden into image using steganography technology, and will be transferred to server security without any hacker problem. And then, our authentication server only needs to store only a secret key for decryption instead of large password database.